Industrial Location in Chinese Provinces: Does Energy Abundance Matter? - Grether, Jean-marie; Mathys, Nicole; Hotz, Irina (My University, 2014)
We identify the driving factors of manufacturing activity across Chinese provinces with a particular focus on energy endowments. A model of production location is estimated, including both comparative advantage and economic geography determinants. The data set used consists of a panel of 28 Chinese provinces and 12 manufacturing industries over the period 1999-2009. Results confirm the relative importance of energy endowments. We find that larger energy endowments are significantly correlated with larger production of energy-intensive sectors. Disaggregating across energy carriers shows that coal exhibits the strongest impact. These results are robust across alternative specifications.
Keywords: China; industry location; economic geography; energy endowments